Car Wash a Sexist Job in the Peruvian Andes - Gutiérrez-Gómez, Edgar; Munaris-Parco, Sonia Beatriz; Janampa-Patilla, Hubner; Quispe-Arroyo, Adolfo; Auccatoma-Tinco, Roly (Journal of Ecohumanism, 2025)
The objective of the research was to analyze how car wash work in the Peruvian Ande promotes sexist attitudes, especially through advertising featuring half-naked young women. The method used was ethnography, with participant observation and informal interviews, due to the social and informal nature of this type of work. The researchers' integration into the community of car washers, both as clients and as frequent passersby, was key to interacting with workers and clients on public roads, where labor practices are carried out illegally. The information collected was processed through field notes and reflection on the data obtained. It is concluded that informal car wash work in the Peruvian Ande perpetuates sexist attitudes, mainly through sexualized advertising of women. Despite the promotion of gender equity by the central government, local governments minimize these policies to preserve their popularity, which allows the continuity of sexist practices within this informal sector.